2011
DOI: 10.1007/s00066-010-2187-1
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for Treatment of Vertebral Metastases Using Intensity-Modulated Radiotherapy*

Abstract: Based on the present results, we recommend a BED2 of 100 Gy or less at D1cc as a constraint for the spinal cord in previously unirradiated cases, and a cumulative BED2 of 150 Gy or less at D1cc in previously irradiated cases, when the interval was not shorter than 6 months and the BED2 for each session was 100 Gy or less. The prescribed BED10 of 80 Gy could be safely delivered to the vertebral lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The maximum spinal cord dose in a very small volume is, thus, likely to be blurred. Inoue et al [17] report on 1 patient with D 0.5cm3 of 127 Gy (BED 2 ) to the cervical spine with a transient myelitis, however, after re-irradiation [17]. To our knowledge, no dose-volume response data of the spinal cord with regard to LS are known in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…The maximum spinal cord dose in a very small volume is, thus, likely to be blurred. Inoue et al [17] report on 1 patient with D 0.5cm3 of 127 Gy (BED 2 ) to the cervical spine with a transient myelitis, however, after re-irradiation [17]. To our knowledge, no dose-volume response data of the spinal cord with regard to LS are known in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…Prognostic factors predicting survival may On multivariate analysis of functional outcome, improved functional outcome was significantly associated with female gender, ECOG-PS 1-2, involvement of only 1-2 vertebrae, no visceral metastases at the time of RT, and a slower development of motor deficits before RT. Thus, four new independent prognostic factors were identified when compared to our previous study of 252 patients published in 2006 [2]. In our previous study, the time developing motor deficits was the only significant predictor of functional outcome (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy (RT) alone is the most common treatment for metastatic spinal cord compression (MSCC) [1,2,6,7,13,15]. Patients with non-small cell lung cancer (NSCLC) account for more than 15% of all patients developing MSCC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Agarawal et al, (28) reported results from a meta-analysis of radiotherapy data finding that one month after treatment, over 40% of patients were likely to have 50% reduction in pain but that fewer than 30% were expected to have complete pain relief. Stereotactic single fraction "radio-surgery" has shown promise (29) and such new approaches for the treatment of vertebral metastases using very steep dose gradients from intensity-modulated radiotherapy (IMRT) have been proposed (30).…”
Section: Treatmentmentioning
confidence: 99%